Analysis of patients with drug‐induced pemphigoid using the Japanese Adverse Drug Event Report database. Issue 3 (21st December 2018) - Tanaka, Hiroyuki; Ishii, Toshihiro
Abstract: To clarify the incidence of drug‐induced pemphigoid in Japan, we conducted a database search and analysis using the Japanese Adverse Drug Event Report database (JADER). Among the cases recorded in JADER between April 2004 and November 2017, we targeted "pemphigoid" and analyzed the patients' backgrounds, drug involvement, time of pemphigoid onset, outcomes and year reported. For cases where three or more drugs were reportedly involved, the signal index was calculated using the reporting odds ratio (ROR) method. The total number of reported pemphigoid cases was 769. Males accounted for 58% (446 cases) and patients over the age of 60 years accounted for 82% (630 cases). The most frequently reported causative drug was vildagliptin (288 cases), followed in order by sitagliptin phosphate hydrate (102 cases), teneligliptin hydrobromide hydrate (86 cases), linagliptin (64 cases) and furosemide (46 cases). For the 27 causative drugs, the safety signal was detected by the ROR method. The median time to onset tended to be long for these drugs. For vildagliptin with the largest reported number, the value was 508 days (range, 2–1871). Analysis of outcomes demonstrated recovery or improvement in 66.3% of cases. Analysis of the years in which reports had been published revealed that the number of pemphigoid cases has increased rapidly in recent years. Our survey was able to reveal useful data on the incidence of drug‐induced pemphigoid. We expect that these results will aid the early detection and treatment of this condition.